The knowledge of mothers in Poland on measles and its prevention - a survey study - Korzeniowska, Anna; Ręka, Gabriela; Piecewicz-Szczęsna, Halina (Journal of Education, Health and Sport, 2020)
Introduction and purpose: Measles is a highly contagious childhood rash disease. An effective way to prevent it is to give two doses of MMR vaccine. An increase in both the incidence of measles and vaccine refusal is observed.The aim of the study is to assess the knowledge of mothers having children under 18 years old about measles and MMR vaccination. It was decided to determine whether measles may turn out to be a threat to the population of our country. Material and methods: A survey questionnaire has been made, which was disseminated on social networks in spring 2020. A total of 537 answers were collected. Data analysis was performed using MS Excel and Statistica. The results were compared with the literature from the last 5 years from PubMed and ResearchGate databases. Results: The average test result was 10.33 out of 17 points. The questions with the highest number of correct answers concerned the obligation, the method of vaccine administration, the etiology of the disease and the method of infection. The problematic questions was the symptoms of measles, complications or the ways of preventing the disease. 8.6% of respondents said that they did not vaccinate their childaccording to the vaccination calendar, giving real contraindications and unreasonable reasons. It was shown that education, place of residence and age of the respondent statistically significantly affect the level of knowledge about measles. There was no correlation between the fact of vaccination and the level of knowledge about measles. Conclusions: The level of knowledge of respondents is mediocre. Parents should receive reliable information about the threats of infectious diseases. Considering presented data, the disease may be a threat to the population of our country.